2022
DOI: 10.12659/msm.934886
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Trajectory and Its Influencing Factors in Chinese Adults: A Cohort Study with Long-Term Follow-Up

Abstract: Background Few studies have been reported on the factors affecting the trajectory of blood pressure in Chinese adults. This study aimed to identify the pattern of blood pressure trajectories and analyze the factors affecting different trajectories. Material/Methods A total of 749 participants were included in this study from the China Health and Nutrition Survey (CHNS) database, collected between 1989 and 2006, and were followed up until 2015. A group-based trajectory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In a recent study of Chinese adults that explored the factors that influence BP trajectories, the participants were divided into three groups based on the SBP trajectory. Among them, an age of ≥40 years, male sex, a BMI of ≥24 kg/m 2 , and Eastern region location were potential factors that influenced the rapid increase in the SBP trajectory and high baseline SBP [ 15 ]. In addition, other studies have reported that lifestyle [ 16 ], fasting blood glucose level [ 17 ], and blood lipid levels [ 18 ] are also closely related to the BP level.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of Chinese adults that explored the factors that influence BP trajectories, the participants were divided into three groups based on the SBP trajectory. Among them, an age of ≥40 years, male sex, a BMI of ≥24 kg/m 2 , and Eastern region location were potential factors that influenced the rapid increase in the SBP trajectory and high baseline SBP [ 15 ]. In addition, other studies have reported that lifestyle [ 16 ], fasting blood glucose level [ 17 ], and blood lipid levels [ 18 ] are also closely related to the BP level.…”
Section: Introductionmentioning
confidence: 99%